ROBUST DECISION MAKING (RDM) INVESTIGATION IN WATER RESOURCES PLANNING AND DISASTER MITIGATION IN MAKASSAR CITY, INDONESIA - Zakir Sabara; Rahmad Junaidi; Rofiqul Umam (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
The Kota Makassar water utility serving (Perusahaan Daerah Air Minum - PDAM) faces a significant problem in managing water resources for their drinking water supply. The problems comprise raw water supply, the vulnerability of water quality, infrastructures, costs, and climate change uncertainty. The availability of clean water is one of the problems in the field of national defense. Because water is the main source of life in all sectors, be it agriculture or livestock. This study is aimed at assisting officials in making an adaptive and resilient decision. It involves inter-and cross-disciplinary studies within Robust Decision-Making (RDM) in water resources management planning for drinking water supply and disaster mitigation in Makassar. This research applies a qualitative approach in data analysis; reviewing strategies used by the utility management to anticipate all uncertainty, long-term strategies feasibility from simulation models, analyzing potential vulnerability scenarios, and the trade-off for an adaptive and robust decision in water resources management planning for drinking water supply in Makassar through RDM. The novelty lies in the raw water management policy that is more adaptive toward potential vulnerability and presents a variety of raw water supply alternatives in the long term. Reviews against the document of drinking water Master Plan found that the absence of harmony along with a high level of anticipation towards the threat of climate change along with their impact, as well as the threat of the raw water supply limitations due to the exogenous problems beyond the reach of human beings capacity, will result in global and long-term impact.